Early Oral Language Comprehension, Task Orientation, and Foundational Reading Skills as Predictors of Grade 3 Reading Comprehension. Issue 4 (1st April 2016) - Lepola, Janne; Lynch, Julie; Kiuru, Noona; Laakkonen, Eero; Niemi, Pekka
Abstract: The present five‐year longitudinal study from preschool to grade 3 examined the developmental associations among oral language comprehension, task orientation, reading precursors, and reading fluency, as well as their role in predicting grade 3 reading comprehension. Ninety Finnish‐speaking students participated in the study. The students' oral language comprehension (vocabulary knowledge, listening comprehension, and inference making) and task orientation were assessed in preschool, kindergarten, and grade 3. Reading precursors (letter knowledge and phonological awareness) were assessed at the first two timepoints and reading fluency at the third timepoint. Structural equation modeling showed that oral language comprehension, reading fluency, and task orientation each contributed uniquely to concurrent reading comprehension, and together they accounted for 76% of variance in reading comprehension. A reciprocal relationship was found between oral language comprehension and task orientation from preschool through kindergarten to grade 3, a finding that extends our knowledge of the longitudinal determinants of reading comprehension.